2019
DOI: 10.1371/journal.pone.0210286
|View full text |Cite
|
Sign up to set email alerts
|

Continuous, quantifiable, and simple osmotic preconcentration and sensing within microfluidic devices

Abstract: Insurmountable detection challenges will impede the development of many of the next-generation of lab-on-a-chip devices (e.g., point-of-care and real-time health monitors). Here we present the first membrane-based, microfluidic sample preconcentration method that is continuous, quantifiable, simple, and capable of working with any analyte. Forward osmosis rapidly concentrates analytes by removing water from a stream of sample fluid. 10-100X preconcentration is possible in mere minutes. This requires careful se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…If the osmolarities of both the incoming sample and the draw solution are known, this approach can be rendered more predictable in the amount of preconcentration achieved by allowing the sample stream and the osmotic draw solution to equilibrate in osmolality before reaching the sensor. However, allowing for equilibrium in osmotic strengths limits the input flow rate 29 and can impact the sensor performance (by changing pH or salinity).…”
Section: Considerations/issues With Membrane-based Concentrationmentioning
confidence: 99%
See 4 more Smart Citations
“…If the osmolarities of both the incoming sample and the draw solution are known, this approach can be rendered more predictable in the amount of preconcentration achieved by allowing the sample stream and the osmotic draw solution to equilibrate in osmolality before reaching the sensor. However, allowing for equilibrium in osmotic strengths limits the input flow rate 29 and can impact the sensor performance (by changing pH or salinity).…”
Section: Considerations/issues With Membrane-based Concentrationmentioning
confidence: 99%
“…As the results of this study (all of the work in this section) have already been published, the full details of the study have been omitted and can be found in the original publication. 29 However, the main testing procedure and results are summarized here in order to allow for a thoughtful discussion on the method's potential in diagnostics.…”
Section: Example Success For Osmotic Concentrationmentioning
confidence: 99%
See 3 more Smart Citations